2019
DOI: 10.1186/s13018-019-1119-8
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inhibits the osteogenesis of fibroblasts in ultrahigh molecular weight polyethylene (UHMWPE) wear particle-induced osteolysis

Abstract: BackgroundIn the ultrahigh molecular weight polyethylene (UHMWPE) prosthetic environment, fibroblasts affected by wear particles have the capacity of osteogenesis to reduce osteolysis. We aimed to assess the effects of macrophages on the osteogenic capability of fibroblasts treated with UHMWPE wear particles.MethodsThe effect of different concentrations of UHMWPE (0, 0.01, 0.1, and 1 mg/ml, respectively) on macrophage proliferation were validated by MTT assay to determine the optimum one. The fibroblasts viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…There is strong evidence for the critical role of chronic low-grade inflammation in the mechanism of PPOL [7][8][9]. The evidence comes from in vitro studies [10][11][12][13][14], in vivo experiments [15][16][17][18][19], and analysis of tissues harvested during reoperations [20][21][22][23]. It has been repeatedly demonstrated in vitro and in vivo that after contact between artificially prepared prosthetic byproducts and immune cells, the latter express pro-inflammatory cytokines, chemokines and other substances ( Figure 1).…”
Section: The Case Of Inflammatory Osteolysismentioning
confidence: 99%
“…There is strong evidence for the critical role of chronic low-grade inflammation in the mechanism of PPOL [7][8][9]. The evidence comes from in vitro studies [10][11][12][13][14], in vivo experiments [15][16][17][18][19], and analysis of tissues harvested during reoperations [20][21][22][23]. It has been repeatedly demonstrated in vitro and in vivo that after contact between artificially prepared prosthetic byproducts and immune cells, the latter express pro-inflammatory cytokines, chemokines and other substances ( Figure 1).…”
Section: The Case Of Inflammatory Osteolysismentioning
confidence: 99%
“…Many UHMWPE structures are sterilized by gamma irradiation at room environment. This has subsequently been shown to cause oxidative degradation of the polymer both in vitro and in vivo leading to an increased wear rate and release of polymeric debris [79,80]. Some studies have reported a lower friction when a highly cross-linked polyethylene (XLPE) counter-body was used instead of UHMWPE against CoCr-based surfaces [78,81].…”
Section: Degradation Of Tmj Tjr Componentsmentioning
confidence: 99%
“…Immediately on implant placement, synthetic materials spontaneously adsorb a layer of host proteins that mediate the interaction with immune cells (e.g., macrophages, neutrophils). For instance, macrophages interact with wear particles through the layer of adsorbed serum proteins, including type I collagen, aggrecan proteoglycans, immunoglobulin, fibronectin and albumin (Figure 3) [80,88]. It is well-known that UHMWPE particles in the 0.1-1.0 µm size range have been shown to be more biologically reactive than larger particles.…”
Section: Adverse Biological Effects Of Debris Released From Tmj Tjrmentioning
confidence: 99%
“…Durante o processo de degradação, também partículas de UHMWPE podem ser libertadas, apresentando um formato de grânulos, lascas ou flocos, em vez do formato de agulha observado nos materiais metálicos. (Lei et al, 2019;Zaveri et al, 2017). A alteração das superfícies de contacto é uma das formas de diminuir o desgaste.…”
Section: Degradação Das Próteses E Riscos De Toxicidade Aos Pacientesunclassified